Implementation of Assessment Principles, Performance, and Client Satisfaction of Municipal Assessment Offices in Negros Occidental, Philippines - Tumbagahan, Jennifer S.; Caelian, Merlita V.; Caelian, Zeaphard Gerhart V. (Philippine Social Science Journal, 2021)
Accurate implementation of real property assessment principles strengthens real property taxation resulting in improved performance towards client satisfaction. This study assessed the implementation of assessment principles, the performance, and the satisfaction of clients of municipal assessment offices in Negros Occidental, Philippines. It likewise determined the challenges encountered by offices. A descriptive-comparative design was utilized using researcher-made survey instruments administered to assessors and randomly selected staff and clients. Using descriptive and inferential analyses, the findings revealed a very great extent of implementation with no significant differences across all areas when municipalities were grouped as to variables of income classification and land area. While the level of performance was outstanding as a whole, with no significant difference in all areas when grouped as to income class, a significant difference was revealed when assessment offices were grouped as to land area. Clients were very satisfied with assessment services with no significant difference in physical setup when grouped into income classes. However, there were significant differences in frontline services, service quality, physical setup, and basic facilities. While when grouped as to land area, there was a significant difference across all areas. Several challenges were encountered by assessment offices, such as the agrarian reform program, administrative, policies, and political concerns. The study recommends a review of some policies specifically on the preparation and approval of the schedule of market value.